Characterization of the Antigenic Determinants of Cholera Toxin Subunits - Markel, Daiel E. (1979)
The antigenic specificity of purified preparations of A subunit, B subunit, α chain, and γ chain of cholera toxin was studied by double immunodiffusion and radioimmunoassay with antisera produced in rabbits and mice. Rabbits immunized with A subunit produced serum antibodies which were capable of binding radiolabeled A subunit, α chain, and B subunit. Rabbits immunized with α chain produced serum antibodies that would bind radiolabeled α chain and A subunit. Rabbits immunized with the B subunit produced serum antibodies monospecific for the B subunit. The γ chain did not elicit measurable antibodies in rabbits or mice as evidenced by radioimmunoassay or double immunodiffusion. A sensitive competitive radioimmunoassay was developed in which the B subunit could inhibit binding of radiolabeled A subunit and α chain with either antisera prepared against A subunit or α chain. Neither the A subunit nor the α chain could inhibit binding of B subunit with the antiserum prepared against B subunit. In addition, selected elution fractions obtained during A- and B-subunit purification were used to immunize groups of mice. Mice responded to immunization with the elution fractions of A subunit by producing anti-A-subunit and anti-B-subunit serum antibody responses, whereas mice immunized with elution fractions of B subunit produced only antibodies specific for the B subunit. An equimolar amount of the two resulting protein peaks was used to immunize two groups of rabbits. Rabbits immunized with A subunit, produced a serum anti-B subunit response equal to that of rabbits immunized with the B subunit. Rabbits immunized with equimolar concentrations of A and B subunits were observed to be equally protected against intestinal loop challenge with Vibrio cholerae Inaba V86. The A subunit, not the B subunit, was biologically active when tested by the S49 mouse lymphosarcoma cell test. These studies provide additional evidence supporting the hypothesis that the A subunit, specifically of α chain, of cholera toxin contains antigenic determinants in common with the B subunit.